STUDENTS PERCEPTION TOWARD ETHICS OF ISLAMIC DRESS (A Case Study in IAIN Ambon) - Muslim Muslim (Universitas Brawijaya, 2020)
This research is based on the phenomenon of female students dressed at IAIN Ambon with a dress style that is contrary to syar'i rules as taught in Islamic teachings. As an Islamic education institution, IAIN Ambon should have guidelines for dress ethics for female students that do not deviate from Islamic teachings. This study aims to understand how female students' perceptions of dress ethics in Islamic law, especially those of students at the Faculty of Tarbiyah and Teacher Training (FITK) in the Islamic Religious Education Department (PAI) at IAIN Ambon, who are Islamic religious teacher candidates. By using qualitative descriptive methods, through observation, interview, and documentation techniques, this study found that in general the FITK PAI students had a relatively good perception of the rules of Islamic dress. It's just that some of their attitudes and dress practices are more predominantly influenced by theenvironment so that they change their choice of dress styles whether syar'i or non-syar'i (islamic or non-Islamic). This research also proves that the perception of clothing has a correlation with the act of dressing, but it does not apply automatically. The fact that the practice of dress is not Islamic is due to the weak influence of religious education in the familyand promiscuity environment.